Pengaruh variasi laju aliran dan preheating cetakan pada investment casting terhadap sifat fisis dan mekanis prototipe aluminium cylinder head engine - Masy'ari Masy'ari; Ari Dwi Prasetiyo; Edi Karyadi; Iyus Iyus (TURBO [Tulisan Riset Berbasis Online], 2022)
This research studies the effect of flow rate on the pouring of molten metal into the mould so that the flow rate into the mould can be controlled. Furthermore, this research studies the effect of mould preheating so that the temperature inside the cavity can be maintained, especially for narrow holes. The process starts with making the engine cylinder head pattern and gating system using a three-dimensional printer with polylactic acid resin. The mould pattern and gating system are combined and coated with a layer of cement plaster, silica sand and kaolin. After the coating is dry, the mould is heated until the mould pattern evaporates and there is no residue. The casting process was carried out at pre-heating moulds of 300 0C and 350 0C and a pouring temperature of 800 0C with pouring speeds of 20, 30, and 40 rpm. The final stage of the research is manufacturing test objects and testing mechanical properties. The results showed that the higher the pouring speed, the less perfect the casting results, especially in the cylinder head fins. The best casting results occurred in the pre-heat condition of the 300 0C mould with a pouring speed of 20 rpm, with a Maximum Tensile Strength of 105 N/mm2, Hardness 53 hardness Brinell test (HBN), Density and Porosity of 2.43 gr/cm3. The material used in this study refers to the reference is A356 Aluminum Alloy.